Understanding satellite navigation - Acharya, Rajat (Academic Press, 2014)
This book explains the basic principles of satellite navigation technology with the bare minimum of mathematics and without complex equations. It helps you to conceptualize the underlying theory from first principles, building up your knowledge gradually using practical demonstrations and worked examples. A full range of MATLAB simulations is used to visualize concepts and solve problems, allowing you to see what happens to signals and systems with different configurations. Implementation and applications are discussed, along with some special topics such as Kalman Filter and Ionosphere. W.